Early atypical malignant transformation of diffuse low-grade astrocytoma: The importance of genotyping - Valente Aguiar, P (2022)
Diffuse astrocytoma (WHO grade II) has classically been considered a slow growing tumour, typically affecting young adults, with tendency for late malignant conversion. We describe a case of early atypical malignant transformation of diffuse astrocytoma seventeen months after complete surgical removal, as an intraventricular high-grade glioma (HGG). Retrospective laboratory findings for the presence of IDH 1/2 (isocitrate dehydrogenase) mutations were negative. There is growing evidence that IDH-wildtype (wt) astrocytomas behave more aggressively, therefore identifying IDH-mutation status should be mandatory in order to determine disease prognosis and guide treatment course.